2019
DOI: 10.1055/s-0039-1693472
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-Associated Thrombosis: A Two-Way Street

Abstract: Pathological activation of the coagulation system occurs with virtually all forms of cancer, particularly epithelial malignancies. Accordingly, thrombosis is one of the most common comorbidities associated with cancer. Indeed, cancer-associated thromboembolism is the second leading cause of death for cancer patients, second only to the cancer itself. The identification of specific molecular mechanisms whereby tumor cells activate the coagulation system and drive thrombosis has been an active area of investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 115 publications
0
37
0
1
Order By: Relevance
“…Beyond frankly thrombotic pathologies, the recent meta-analysis performed by Pyo and colleagues also concluded that MPV is significantly increased in cancer patients compared to healthy controls (mean difference, 0.50 fL; 95% CI, 0.28-0.72 fL), whilst its value significantly decreases in post-treatment patients [44]. This is an important information that contributes to explain the considerably higher burden of thrombotic disorders in patients with malignant diseases [45], as well as the putative interplay between platelet and cancer biology [46].…”
Section: Discussionmentioning
confidence: 94%
“…Beyond frankly thrombotic pathologies, the recent meta-analysis performed by Pyo and colleagues also concluded that MPV is significantly increased in cancer patients compared to healthy controls (mean difference, 0.50 fL; 95% CI, 0.28-0.72 fL), whilst its value significantly decreases in post-treatment patients [44]. This is an important information that contributes to explain the considerably higher burden of thrombotic disorders in patients with malignant diseases [45], as well as the putative interplay between platelet and cancer biology [46].…”
Section: Discussionmentioning
confidence: 94%
“…Venous thromboembolism (VTE) events are common among cancer patients, and their occurrence contributes significantly to morbidity and mortality. 8,9 The risk of VTE is increased by fiveto sevenfold among patients with malignant diseases, while fatal PE is three times more common in this population relative to noncancer patients. Annually, 0.5% of cancer patients experience thrombosis compared with a 0.1% incidence rate in general population.…”
Section: Thrombosis and Cancermentioning
confidence: 99%
“…Взаимодействие между опухолевой тканью, системой гемостаза и иммунной системой происходит по типу каскада взаимной активации, тем самым приводя к формированию порочного круга. Прикрепляясь к сосудистому эндотелию, опухолевые клетки, активируют коагуляционный каскад напрямую посредством тканевого фактора, а также индукции воспалительных цитокинов [22,25,26]. Активация тромбином активируемых протеазами рецепторов может привести к пролиферации субинтимы эндотелия и гладких мышц.…”
Section: A R T I C L E I N P R E S Sunclassified